Volatility Management in Multifactor Portfolios: A Literature Review on Risk-Return Dynamics and Strategic Investment Implications - Ruslaini Ruslaini; Muhammad Rizal; Sri Utami Nurhasanah (Cahaya Abadi Publisher, 2025)
This study aims to review the challenges faced in the risk-return relationship within multifactor portfolios, with a focus on the implications for market volatility management. Through a literature review, this research identifies various factors that influence volatility and how volatility management can enhance portfolio performance. The analysis reveals that while multifactor portfolios offer advantages in diversification and risk management, market volatility remains a key challenge in achieving a balance between risk and return. This study also uncovers that active volatility strategies outperform passive ones, but they require a deep understanding of market dynamics. The implications of this research provide insights for portfolio managers in designing investment strategies that are more adaptive to high market volatility.